2018
DOI: 10.1371/journal.pone.0194431
|View full text |Cite
|
Sign up to set email alerts
|

Increased ethanol consumption after interruption of fat bingeing

Abstract: There is a marked comorbidity between alcohol abuse and eating disorders, especially in the young population. We have previously reported that bingeing on fat during adolescence increases the rewarding effects of ethanol (EtOH). The aim of the present work was to study if vulnerability to EtOH persists after cessation of binge eating. OF1 mice binged on fat (HFB: high-fat binge) during adolescence (PND 25–43) and were tested for 15 days after the last access to HFB (on PND 59) using the self-administration par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 73 publications
0
7
0
Order By: Relevance
“…The HFDb-S group exhibited an increased alcohol consumption compared to the SD-S group. Previous experiments in our laboratory showed that ethanol consumption is increased by HFD bingeing during adolescence [ 58 , 81 ]. The repeated stimulation of the reward system during episodes of HFD bingeing influences the dopaminergic signaling [ 82 , 83 , 84 , 85 ].…”
Section: Discussionmentioning
confidence: 99%
“…The HFDb-S group exhibited an increased alcohol consumption compared to the SD-S group. Previous experiments in our laboratory showed that ethanol consumption is increased by HFD bingeing during adolescence [ 58 , 81 ]. The repeated stimulation of the reward system during episodes of HFD bingeing influences the dopaminergic signaling [ 82 , 83 , 84 , 85 ].…”
Section: Discussionmentioning
confidence: 99%
“…Motivation to seek drugs of abuse and highly palatable foods is regulated by the reward system [ 1 ]. Previous studies have shown psychological and biological commonalities between palatable food intake and drug addiction [ 2 , 3 ] and recent studies have indicated that nutritional habits are an important modulating factor in the development of cocaine [ 4 , 5 ] and alcohol addiction [ 6 , 7 ]. Palatable diets change metabolism and the reward system by increasing vulnerability to the rewarding effects of psychostimulants and depressants, such as cocaine and alcohol [ 4 , 6 , 8 ], but little is known about the protective effects that nutrition could have in the development of drug addiction.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, when we made the task required to obtain the drug more difficult (by increasing the number of required nose pokes), these animals showed more motivation to receive the drug (Blanco-Gandía et al, 2018). Not only did they consume more, but they also worked harder to get it.…”
Section: «Potentially Addictive Substances Like Cocaine and Other Drugs Are Often The Results Of Manipulations And Refining Processes Thamentioning
confidence: 96%